Epidemiological profile of neonates with transposition of the great arteries in Brazil between 2010 and 2022 (Research, Society and Development, 2025)
Introduction: The cardiovascular system is crucial for human development since the embryonic phase, being essential for the understanding of congenital heart diseases, such as transposition of the great arteries (TGA), where the main arteries of the heart are inverted, compromising blood oxygenation. Objective: To explore the epidemiological profile of neonates diagnosed with transposition of great arteries in Brazil between 2010 and 2022. Methodology: This is a descriptive and retrospective epidemiological study with a quantitative approach. Data from the Live Birth Information System (SINASC), accessed via DATASUS, were analyzed, covering neonates diagnosed with TGA in Brazil from 2010 to 2022. Results and Discussion: A total of 521 live births with TGA were identified. Most mothers (64.1%, n=334) were between 25 and 34 years old, (72.6%, n=378) started prenatal care in the first trimester, and (77.0%, n=401) attended seven or more consultations. The cesarean section rate was (78.7%, n=410), and (84.5%, n=440) of the neonates were born at term, with (85.2%, n=444) having an adequate birth weight. However, (35.5%, n=185) of newborns showed some degree of asphyxia at the 1st minute and (14.1%, n=72) at the 5th minute according to the Apgar score. Conclusion: The study highlights the importance of prenatal monitoring and early diagnosis to reduce morbidity and mortality associated with transposition of the great arteries.